Case Report: Exacerbation after fat grafting in patients with active localized scleroderma - Han, Shunxin; Liu, Juzi; Lu, Feng; Cai, Junrong (Frontiers in Surgery, 2024)
BackgroundThe application of autologous fat transplantation in facial lesions of patients with localized scleroderma (LoS) has been reported in recent years.ObjectiveThe authors report a case of worsening of active localized scleroderma after autologous fat transplantation.MethodsA man presented with neck and facial skin atrophy and pigmentation with a history of LoS. Appearing 1.5 years ago, the lesion had progressively grown in size and shape. Consent was obtained after the patient was informed of the possible surgical risks during the active phase of the disease. He underwent autologous fat grafting into the right cheek with about 30 ml Coleman fat graft.ResultsSkin dyspigmentation and atrophy progressively deteriorated 1 month into therapy, with slightly increased erythema and enlargement of the lesion. Six months after the therapy, the localized scleroderma-related score worsened.LimitationsThere are different factors, such as that systemic medications could affect the treatment of localized scleroderma by autologous fat transplantation. Meanwhile, considering the limitation of the 6-month follow-up period, obtaining long-term follow-up data is necessary to evaluate sustained outcomes and potential complications.ConclusionMore clinical research is needed to determine the time interval between disease inactivity and the application of any surgical procedures to avoid reactivation.